Anti-Inflammatory Effects of Heliangin from Jerusalem Artichoke (Helianthus tuberosus) Leaves Might Prevent Atherosclerosis - Papawee Saiki; Mizuki Yoshihara; Yasuhiro Kawano; Hitoshi Miyazaki; Koyomi Miyazaki (Biomolecules, 2022)
Atherosclerosis is considered the major cause of cardiovascular and cerebrovascular diseases, which are the leading causes of death worldwide. Excessive nitric oxide production and inflammation result in dysfunctional vascular endothelial cells, which are critically involved in the initiation and progression of atherosclerosis. The present study aimed to identify a bioactive compound from Jerusalem artichoke leaves with anti-inflammatory activity that might prevent atherosclerosis. We isolated bioactive heliangin that inhibited NO production in LPS-induced macrophage-like RAW 264.7 cells. Heliangin suppressed ICAM-1, VCAM-1, E-selectin, and MCP-1 expression, as well as NF-κB and IκBα phosphorylation, in vascular endothelial cells stimulated with TNF-α. These results suggested that heliangin suppresses inflammation by inhibiting excessive NO production in macrophages and the expression of the factors leading to the development of atherosclerosis via the NF-κB signaling pathway in vascular endothelial cells. Therefore, heliangin in Jerusalem artichoke leaves could function in the prevention of atherosclerosis that is associated with heart attacks and strokes.